Iowa Birdline update, December 3, 1990, notes - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1990)
Notes for the Iowa Birdline update for December 3, 1990. Highlights of the notes include an immature male Yellow Grosbeak, Short-eared Owls, a female Merlin, and several hundred Bonaparte's Gulls. Epson - sheet feed/flatbed